Novel agents for advanced pancreatic cancer - Akinleye, Akintunde (Oncotarget, 2015)
Pancreatic cancer is relatively insensitive to conventional chemotherapy. Therefore, novel agents targeting dysregulated pathways (MAPK/ERK, EGFR, TGF-β, HEDGEHOG, NOTCH, IGF, PARP, PI3K/AKT, RAS, and Src) are being explored in clinical trials as monotherapy or in combination with cytotoxic chemotherapy. This review summarizes the most recent advances with the targeted therapies in the treatment of patients with advanced pancreatic cancer.